Coronavirus A book for children. - Scheffler, Axel. (Somerville : Nosy Crow, 2020)
"An elegant, effective work. Download this now, read it immediately, share it with everyone you know." ? School Library Journal (starred review) This informative and accessible guide for young readers defines the coronavirus, explains why everyday routines have been disrupted, and lays out how everyone can do their part to help. With child-appropriate answers and explanations, the book addresses key questions, like: How do you catch coronavirus and what happens if you have it? Why are people so worried about it? Is there a cure? Why do we have to stay home? What can I do to help? And what happens next?
Title from eBook information screen..
Requires .
Keywords: Juvenile Nonfiction; Geography; Health & Fitness; Sociology; Electronic books